(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2021)
Diabetes mellitus is a chronic metabolic disorder that places a huge health and economic burden on societies. Since currently available medications have many drawbacks, it is important to seek alternative therapies. Medicinal plants used in traditional medicine are ideal candidates. Therefore, this study was carried out to investigate the anti-diabetic activity of the stem bark extract of Parkia biglandulosa (mimosaceae) in wister rats. The phytochemical composition of the stem bark extract was qualitatively evaluated using standard procedures. In vivo anti-diabetic activity was performed by using the alloxan-induced diabetes method by orally administering methanolic extract of stem bark at doses of 200 and 400 mg/kg of body weight and profiling blood glucose levels at 0, 7, 14, 21 days using a glucometer. Biochemical parameters such as cholesterol, high-density lipoproteins, low-density lipoproteins, creatinine, urea and alkaline phosphatase were also evaluated. P. biglandulosa stem bark extract at the tested dose levels of 200 and 400 mg/kg showed a significant reduction in blood glucose level with 175.34 ± 9.357 and 171.69 ± 6.248 mg/dL respectively as compared with diabetic control grouP. The observed anti-diabetic activity could be associated with the phytochemicals present in this plant extract. The results suggest that P. biglandulosa bark extract possess anti-diabetic activity and this validates its folkloric use.